The role of cultural distance on expatriate's multicultural personality and cross-cultural adjustment / Awang Rozaimie Awang Shuib … [et.al.]. - Awang Shuib, Awang Rozaimie; Sahari, Siti Huzaimah; Morni, Affidah (2016)
Different parts of the world are offering sojourners with a variety of socio-cultural experiences. The inability to understand the variation triggers psychological, physical or behavioural difficulties, maladjustment or misunderstanding. Cross-cultural underestimation is the root of intercultural resistance, stereotyping, ethnocentrism and racism sentiments among sojourners. The online survey was conducted in the present study to comprehend the role of multicultural personality traits on sojourners' cross-cultural adjustment. With snowball method and a purposive sampling, 55.5% of the response rates were obtained among Malaysian sojourners in New Zealand. Basically, the manifestation of self and other's affection, behavioural and contextual variations amplify the rationalisation and contradictory nature of cultural variation.